Credit Crunch and Monetary Policy During Covid-19 Pandemic - HS, M. Rayyan; Sugiharso Safuan (Universitas Airlangga, 2023)
Under crisis conditions, the significant decline in bank credit growth is associated with the credit crunch phenomenon. The ability of the banking system to provide credit in the economy is limited compared to the demand for credit. During the Covid-19 pandemic, credit growth in Indonesia reached its lowest point when compared to the pre-Covid-19 period. However, the causative factor is still ambiguous. Using a credit market disequilibrium model estimated with Maximum Likelihood, this study tested whether the decline in credit during the Covid-19 pandemic was a credit crunch phenomenon. The results of this study show that the parameter of the probability of credit decline during the Covid-19 pandemic is an insignificant credit crunch phenomenon. This means that the estimated demand for credit is less than the excess supply. Thus, the implications for the role of monetary policy by lowering interest rates have been hampered due to the decline in economic activity during the Covid-19 pandemic.